The Legal Regulation of the Proprietary Rights in the People’s Republic of China: Comparison with Russian Law - A. V. Medvedev (Московский журнал международного права)
The article is devoted to the analysis of the Law of the People’s Republic of China “On proprietary rights” which is compared in the basic points with relevant Russian legislation (mainly Civil Code of Russia). The following legal institutes are considered in the article: proprietary rights and ways of their protection, proprietary security rights/their enforcement (mortgage, retention), ownership right (definition, kinds), possession right.Currently the Chinese civil law is actively developing. The new legislative acts are regularly adopted. The Law “On proprietary rights” along with several other Chinese laws (General Provisions of the Civil Law, Contracts Law, Prices Law, Security of Performance of Obligations Law, Foreign Trade Law, Arbitration Law etc.) aim to establish the legal basis for market economy development. Most of these acts will definitely form someday the Civil Code of China.The article may be useful for lawyers working with Chinese civil law and may be used for scientific purposes as well as it reviews one of the basic Chinese civil laws in comparison with similar Russian acts, revealing similar things and differences, advantages and disadvantages in legislative regulation of the considered issues in the two legal systems.